Women in geology. Elena Alexandrovna Moldavskaya (1891-1973) - I. A. Starodubtseva (Известия высших учебных заведений: Геология и разведка, 2019)
E.A. Moldavskaya was one of the first Russian women-geologists engaged in practical geology. In 1918, she graduated from the Moscow Women's Courses of Higher Education in geology and worked for about 40 years in the chosen profession. E.A. Moldavskaya controlled geological and engineering-geological researches in Moscow region, Volga region, Belarus. She was engaged in exploration and evaluation of ratovkite, limestone, clay, gypsum deposits, and compiled a summary «Mineral resources of the gypsum industry of the USSR». E.A. Moldavskaya supervised the theme «Assessment of the gas potential prospects in Moscow and Moscow region», took part in geological survey for thermal power plants and made the instruction on researches of constructional materials for construction of those plants. E.A. Moldovskaya was awarded by medal «For Valorous Labour in the Great Patriotic war» (1946), «In memory of the 800th anniversary of Moscow» (1948). The professional activities and biography of E.A. Moldavskaya have been considered for the first time.